G. BROWN'S ACCESSION TO POWER AND THE RELATIONS OF GREAT BRITAIN WITH THE USA IN 2007-2008 - A. Balayan (Гуманитарные и юридические исследования)
The article studies the relations of Great Britain with the USA after of the Labour government led by Prime Minister G. Brown came to power in June 2007. New British government had to take into consideration the public opinion, the British expressed discontent with excessive dependence of British foreign policy on the USA and the participation of London in the Iraq war. The article shows that G. Brown belonged to a number of supporters of maintaining "special relations" with the USA, that is why one could not expect any radical changes in London policy with Washington, still the leader was aimed at correcting the foreign policy. G. Brown admitted the strategic role of the USA in maintaining the international security. The author marks that the intention of London to withdraw from Iraq became an essential problem in relations of the government led by G. Brown with the administration of G. Bush. However, Great Britain did not plan any unilateral action as it coordinated its policy in Iraq with the USA. The article shows the intention of new British government to focus mostly on multilateral action with the participation of international organizations in foreign policy. Since 2007, the relations of Great Britain and the USA have been affected by dificulties that, to a large extent, were preconditioned by the global economy context. Both states intended to join forces to tackle the world economic crisis. In conclusion, the author notes the influence of presidential elections in 2008 on further relations of Great Britain and the USA. G. Brown pursued to define a favorite of the election campaign taking into account the importance of establishing the dialogue with the new president of the USA.